Linear Precoding for MIMO Channels with Outdated Channel State Information in Multiuser Space-Time Block Coded Systems with Multi-Packet Reception - Au, E.K.S.; Huang, J.W.; Lau, V.K.N. (IEEE transactions on wireless communications, 2008)
We propose a joint set of linear precoder designs for single cell uplink multiuser space-time block coded multiple- input multiple-output systems with multi-packet reception by exploiting outdated channel state information. By deriving the pairwise error probability with respect to both minimum and average codeword distance design metrics, we formulate the design as an optimization problem subject to transmit power constraint for each user. Due to the non-convex nature of the optimization problem, we devise an iterative algorithm to solve for linear precoding structure for general space-time block code. For orthogonal space-time block code, we also propose a simplified distributed algorithm to solve for a closed-form solution. Asymptotic analysis on the effect of quality of the outdated channel state information (CSI) on the precoder structure is also presented. Simulation results are provided to demonstrate the effectiveness of the proposed designs for different space-time block codes at various CSI qualities.